The Role of Influencer Marketing, Online Customer Reviews, and Brand Reputation on Millennial Purchase Decisions for Fashion Products on Tokopedia - Saputri, Jihan Bella; Huda, Nurul (Manunggal Halim Jaya, 2026)
This study analyzes the role of influencer marketing, online customer reviews, and brand reputation in shaping millennials’ purchasing decisions for fashion products on Tokopedia. Using a quantitative approach with purposive sampling, 147 millennial respondents who had purchased fashion products on Tokopedia were surveyed. Data were collected through an online questionnaire and analyzed with Structural Equation Modeling (SEM-PLS) using SmartPLS 3.0. Results indicate that all three variables significantly influence purchase decisions, with online customer reviews showing the strongest effect, followed by influencer marketing and brand reputation. The term dominant variable refers to the factor with the highest path coefficient in the SEM analysis. These findings highlight the importance of integrating influencer collaborations, user-generated reviews, and brand reputation management to enhance consumer trust and loyalty in highly competitive e-commerce platforms.